Stress fractures of the foot and ankle, part 1: biomechanics of bone and principles of imaging and treatment - Mandell, Jacob C.; Khurana, Bharti; Smith, Stacy E. (Skeletal radiology, 2017)
A stress fracture is a focal failure of bone induced by the summation of repetitive forces, which overwhelms the normal bone remodeling cycle. This review, the first of two parts, discusses the general principles of stress fractures of the foot and ankle. This includes bone structure, biomechanics of stress applied to bone, bone remodeling, risk factors for stress fracture, and general principles of imaging and treatment of stress fractures. Cortical bone and trabecular bone have a contrasting macrostructure, which leads to differing resistances to externally applied forces. The variable and often confusing imaging appearance of stress fractures of the foot and ankle can largely be attributed to the different imaging appearance of bony remodeling of trabecular and cortical bone. Risk factors for stress fracture can be divided into intrinsic and extrinsic factors. Stress fractures subject to compressive forces are considered low-risk and are treated with activity modification and correction of any modifiable risk factors. Stress fractures subject to tensile forces and/or located in regions of decreased vascularity are considered high risk, with additional treatment options including restricted weight-bearing or surgery.